2020
DOI: 10.3390/microorganisms8122039
|View full text |Cite
|
Sign up to set email alerts
|

H89 Treatment Reduces Intestinal Inflammation and Candida albicans Overgrowth in Mice

Abstract: Deregulation of the dynamic crosstalk between the gut microbiota, intestinal epithelial cells, and immune cells is critically involved in the development of inflammatory bowel disease and the overgrowth of opportunistic pathogens, including the human opportunistic fungus Candida albicans. In the present study, we assessed the effect of N-[2-(p-bromocinnamylamino)ethyl]-5-isoquinolinesulfonamide (H89), a protein kinase A inhibitor, on the migration of macrophages to C. albicans through dextran sulphate sodium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…cDNA synthesis was carried out using a High Capacity DNA Reverse Transcription (RT) kit, with Master Mix (Applied Biosystems, CA, USA). To amplify the cDNA, Fast SYBR green (Applied Biosystems) was employed in a one-step system (Applied Biosystems) [ 39 ]. SYBR green dye intensity was assessed using one-step software.…”
Section: Methodsmentioning
confidence: 99%
“…cDNA synthesis was carried out using a High Capacity DNA Reverse Transcription (RT) kit, with Master Mix (Applied Biosystems, CA, USA). To amplify the cDNA, Fast SYBR green (Applied Biosystems) was employed in a one-step system (Applied Biosystems) [ 39 ]. SYBR green dye intensity was assessed using one-step software.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previous results, which showed that H89 reduces intestinal inflammation in a murine model of DSS-induced colitis ( 27 ), we investigated its prophylactic potential. In a mouse model of AOM/DSS colitis-associated intestinal carcinogenesis, we showed that H89 decreases tumor incidence as attested by a significant reduction in the total number of colorectal polyps ( Figures 1A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…The stress responses mediating triazole resistance activate the cyclic AMP (cAMP)-protein kinase A (PKA) signalling pathway [ 91 ]. Dumortier et al showed that N-[2-(p-bromocinnamylamino)ethyl]-5-isoquinolinesulfonamide (H89), a PKA inhibitor, reduced the viability of C. albicans and decreased the expression of pro-inflammatory cytokines and innate immune receptors in colonic epithelial Caco-2 cells and macrophages [ 97 ]. Additionally, H89 decreased colonic inflammation in mice with DSS-induced colitis and allowed elimination of C. albicans from the gut [ 97 ].…”
Section: Role Of Novel Antifungal Compounds On the Modulation Of Infl...mentioning
confidence: 99%
“…Dumortier et al showed that N-[2-(p-bromocinnamylamino)ethyl]-5-isoquinolinesulfonamide (H89), a PKA inhibitor, reduced the viability of C. albicans and decreased the expression of pro-inflammatory cytokines and innate immune receptors in colonic epithelial Caco-2 cells and macrophages [ 97 ]. Additionally, H89 decreased colonic inflammation in mice with DSS-induced colitis and allowed elimination of C. albicans from the gut [ 97 ]. In line with these observations, 2,3-dihydroxy-4-methoxybenzaldehyde (DHMB), a key intermediate in the synthesis of some natural compounds, including the antibacterial agents (±)-isoperbergin and perbergin, was efficient against clinically isolated caspofungin- or fluconazole-resistant C. albicans strains [ 98 ].…”
Section: Role Of Novel Antifungal Compounds On the Modulation Of Infl...mentioning
confidence: 99%